Decolonizing Health Data Literacy: A Systematic Review of Indigenous and Community-Based Mathematical Practices in Health Data Interpretation in Sub-Saharan Africa - Bolouembeledo Fekumo; Moshe M Phoshoko (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Background: Health data systems in Sub-Saharan Africa have been designed largely on Western biostatistical and epidemiological models, which devalue and disregard the Indigenous mathematical practices that communities in the region have used to interpret, communicate, and act on health-related information. This epistemological mismatch results in enduring knowledge gaps within communities, weak effectiveness of public health interventions, and the replication of a colonial knowledge hierarchy in the governance of global health. Aims: This synthesis aims to synthesize the current state of knowledge on the nature and health outcomes of Indigenous and community-based mathematical practices in the interpretation of health data across Sub-Saharan Africa, and to inform decolonial mathematics education curricula and community health data literacy interventions. Methods: This review is reported in accordance with the PRISMA 2020 statement and eMERGe reporting guidelines for meta-ethnography. Nine electronic databases were searched. A meta-ethnographic thematic analysis was used to synthesize findings from 52 studies distributed across West, East, and Southern Africa. Results: The synthesis resulted in three broad clusters of Indigenous mathematical practices: quantifying relationships within the community and using ratios and proportions to describe; epidemiological infrastructure narrated through mnemonic structures that encode and transmit quantitative information about health in community places; and embodied spatial reasoning for the purposes of environmental health surveillance at the community level. In terms of health outcomes, these Indigenous surveillance and monitoring practices allow for an effective community-based approach, but the review shows that there are considerable risks associated with epistemological dissonance. This mismatch between Indigenous norms and Western biomedical norms typically involves not recognizing health issues, such as nutrient deficiencies, or not involving communities in formal health services. Conclusion: The results show that Indigenous mathematical traditions are is a complex and culturally relevant way of understanding, articulating, and acting on health-related information. Integrating community-based relational and spatial reasoning into decolonial mathematics curricula, these results offer crucial evidence base. Moreover, the results inform the design of community health data literacy interventions that are epistemically local and enhance the relevance of health communication and the promotion of epistemic justice in the African public health landscape.